Iconografias da negritude em Salvador - Alberto, Paulina L. (Afro-Ásia, 2022)
Resenha de: ROMO, Anadelia. Selling Black Brazil: Race, Nation, and Visual Culture in Salvador, Bahia. Austin: University of Texas Press, 2022. 348 p.